Till Bisexual Ambiguity: A Multimodal Study in Alien Stage Animation Project - Mahdyah Fitri; Ali Mustofa (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
Representation of bisexuality remains underexplored in contemporary media, particularly when sexual identity is implied rather than explicitly stated. Previous studies have examined gender performativity and queer identities in literary works; however, few have investigated how bisexuality is constructed through multimodal narratives. This study aims to analyze the implied bisexuality of Till in Alien Stage using Judith Butler’s theory of Gender Performativity (1990; 1999; 2004) and Eve Sedgwick’s Epistemology of the Closet (1990). Employing a qualitative descriptive method and multimodal analysis, the study examines visual, verbal, and auditory elements across the series. The findings reveal that Till maintains a consistent masculine gender performance despite emotional attachments to both Mizi and Ivan, while his sexuality is communicated through narrative ambiguity, subtext, and emotional interactions. The study concludes that Alien Stage represents bisexuality through implication rather than explicit identification, challenging heteronormative assumptions about gender and desire.